Ordinance 122441: Establishing a City Immigrant and Refugee Advisory Board - (:unkn) unknown (My University, 2007)
In this Ordinance, the City Council of the City of Seattle establishes a City Immigrant and Refugee Advisory Board by adding new sections to the Seattle Municipal Code.
Keywords: Sanctuary Policies; Subchapter III of Chapter 3.14 of the Seattle Municipal Code; Resolution 30796; Immigrant and Refugee Action Plan; Annual Workplan; Annual Report